2019
DOI: 10.1111/fare.12373
|View full text |Cite
|
Sign up to set email alerts
|

Harsh Parenting and Black Boys' Behavior Problems: Single Mothers' Parenting Stress and Nonresident Fathers' Involvement

Abstract: Objective To test a model linking economic hardship, parenting stress, and nonresident fathers' involvement in single mothers' family life during Black boys' early childhood (3–5 years of age) to harsh parenting and behavior problems in middle childhood (9 years of age). Background Parenting stress among single mothers heading low‐income Black families is poorly understood. Most of the research on the effects of stress in the parenting role and outcomes for mothers and children has focused on middle‐class Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 73 publications
(124 reference statements)
0
20
1
Order By: Relevance
“…The present study examined the associations between parenting stress during toddlerhood and Latinx adolescents’ prosocial and aggressive behaviors approximately 14 years later, as well as whether maternal harsh parenting mediated those associations. Despite evidence for direct associations between parenting stress and aggression (Jackson et al, 2019) and prosocial behaviors (Ward & Lee, 2020), the direct associations may not capture the nuanced manner in which parenting stress affects youth. Based on past literature and the Family Stress model, we hypothesized that parenting stress may spill over into the mother–child relationship and increase harsh parenting practices (Choi & Becher, 2019).…”
Section: Parenting Stress and Adolescents’ Social Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined the associations between parenting stress during toddlerhood and Latinx adolescents’ prosocial and aggressive behaviors approximately 14 years later, as well as whether maternal harsh parenting mediated those associations. Despite evidence for direct associations between parenting stress and aggression (Jackson et al, 2019) and prosocial behaviors (Ward & Lee, 2020), the direct associations may not capture the nuanced manner in which parenting stress affects youth. Based on past literature and the Family Stress model, we hypothesized that parenting stress may spill over into the mother–child relationship and increase harsh parenting practices (Choi & Becher, 2019).…”
Section: Parenting Stress and Adolescents’ Social Behaviorsmentioning
confidence: 99%
“…There is evidence among diverse samples that parenting stress is positively associated with adolescents’ aggressive behaviors both concurrently and over time (Jackson et al, 2019; Krahé et al, 2015; see Morgan et al, 2005). However, longitudinal research on parenting stress in Latinx families is relatively limited.…”
Section: Parenting Stress and Adolescents’ Social Behaviorsmentioning
confidence: 99%
“…While some studies argue that holding multiple roles enhance the person's autonomy, any beneficial effect of multiple role obligations depends on the number, importance and time demands of those roles (Chen et al, 2019:121). In a multiple role situation-for example, the situation of working mothers-role performance and mental well-being are very likely to be impaired if the person cannot separate those roles in time and/or space (e.g., Chen et al, 2019;Jackson et al, 2019;Maeda et al, 2019;Mastrotheodoros et al, 2019). Scheduling tasks and activities is another time-tested form of role compartmentalization beneficial for both parents and children (e.g., Bird and Bird, 1986;Yoon, Newkirk and Perry-Jenkins, 2015) with the proviso of cooperation: the benefits of role compartmentalization increase in tandem with the level of cooperation between the spouses (Lois, 2006) and among all other family members involved.…”
Section: Role Theorymentioning
confidence: 99%
“…Consistently, research has shown that parenting stress is related to a host of undesirable outcomes, both for the parent and the child ( Morris et al, 2017 ). For example, higher parenting stress was found to predict more harsh and hostile parenting ( Chung et al, 2020 ; Jackson et al., 2019 ). Consequently, greater reports of hostile parenting and punitive punishments were found to correlate with increased levels of externalizing behaviors among children ( Bradley & Corwyn, 2007 ).…”
Section: Introductionmentioning
confidence: 99%